Hubungan Kewenangan Presiden dan DPR dalam Sistem Presidensial Indonesia - Ferika Nurfransiska; Nafahatun Nur Khoiriyah; Maisyarah; Sugiono Eksantoso (Lembaga Yasin AlSys, 2026)
The relationship between the authority of the President and the House of Representatives (DPR) is a fundamental element of Indonesia’s presidential system because the two institutions hold complementary and counterbalancing constitutional positions under the UUD NRI Tahun 1945. Although the principle of checks and balances between the President and the DPR has been extensively examined through normative legal research, studies specifically investigating ordinary citizens’ perceptions of the effectiveness of this relationship remain limited, particularly at the regency level. This study aims to measure the level of political literacy and public perceptions of the effectiveness of President–DPR checks and balances in Banyuwangi Regency, analyze differences in perceptions based on respondents’ educational levels, and examine the contribution of political literacy to perceptions of the effectiveness of checks and balances. The study employed a quantitative approach with a descriptive-correlational design and involved 180 respondents selected through purposive-stratified sampling based on educational level across four subdistricts. Data were collected using a five-point Likert-scale questionnaire measuring political literacy and perceptions of the effectiveness of checks and balances and were subsequently analyzed using descriptive statistics, Pearson correlation, simple linear regression, and one-way ANOVA. The results indicate that public perceptions of the effectiveness of checks and balances were in the moderate category, with a score of 54.7 out of 100. The oversight dimension was perceived as the weakest compared with the legislative and budgetary dimensions. In addition, significant differences in perceptions were found based on educational level, while political literacy was positively and significantly correlated with perceptions of effectiveness and accounted for 23.2% of the variance in perceptions of the effectiveness of checks and balances. These findings extend the study of checks and balances in Indonesia, which has thus far been dominated by normative-institutional analyses, by providing an empirical perspective on citizens’ perceptions. This study makes a theoretical contribution to the development of research on constitutional oversight and civic literacy and offers practical implications for designing political education programs at the regional level. This study also provides opportunities for further research with broader geographical coverage and more comprehensive field data.